Seismic interaction in electrical substation equipment connected by non-linear rigid bus conductors. - Song, Junho
An important element within the power transmission lifeline is the electrical substation that typically consists of a complex set of equipment items interconnected through conductor buses or cables. If the connections are not sufficiently flexible, significant dynamic interaction may occur between the connected equipment items during a seismic event, which may result in damage and loss of the equipment. This paper investigates the interaction effect between electrical substation equipment items connected by non-linear rigid bus conductors. The equipment items are modelled as single-degree-of-freedom oscillators by use of appropriate shape functions. The hysteretic behaviours of rigid bus connectors are described by differential equation models fitted to experimental data. An efficient non-linear random vibration method is used to quantify the seismic interaction effect of the connected equipment items. Based on the developed analytical models and method, the effect of interaction in the connected equipment system is investigated through extensive parametric studies. The results lead to practical charts and guidelines for the seismic design of interconnected electrical substation equipment.
Keywords: Dynamic amplification; Dynamic interaction; Electrical equipment; Electrical substation; Equivalent linearization method; Non-linear random vibrations; Rigid bus conductors